Implementing the Next Economy in a Unified Context: A Case Study of the Paddle Prairie Mall Corporation - Robinson, Michael; Ghostkeeper, Elmer (ARCTIC, 1988)
A recent paper entitled "Native and Local Economics: A Consideration of Economic Evolution and the Next Economy" (Robinson and Ghostkeeper, 1987:138-144) by the authors proposed a model for community-based native business development based upon the fusing of community culture with corporate culture in the information and service economy. This model has now been implemented by a Metis entrepreneur in the northern Alberta settlement of Paddle Prairie and is evaluated using the "unified approach" to economic development described by Higgins and Higgins (1979). In this way the new venture's performance is assessed against the following criteria: employment generation, income creation, contribution to regional ecological harmony and maximization of cultural enrichment. It is concluded that the Paddle Prairie Mall Corporation is a practical demonstration of the unified approach in Canada's mid-North and that the "Metis way of doing things," born of the bush economy, is an indigenous Canadian variant of the unified approach that acknowledges the importance of sociocultural and ecological factors in development planning. It remains to be seen whether or not the Metis way of doing things has an Inuit or Indian analogue and to what degree the next economy model can be equally well applied in non-Metis native communities.Key words: community-based economic development, unified development, bush and next (information and service) economies, Metis, case study Mots clés: développement économique au sein la communauté, développement unifié, économie naturelle et prochaine économie (information et services), métis, étude de cas